Prends-moi : le magazine des sexualités gay. (Saint-Denis : INPES.)
Fonds Suzan Daniel (FSD)
Periodiciteit : viermaandelijks?
Redactie : 42 boulevard de la Libération, 93203 Saint-Denis
Frans
Periodiek